Enredando la cuerda: una herramienta pedagógica para la transformación positiva de los conflictos. (2022)
The present research project is focused on developing a pedagogical tool to guide conflicts to their positive transformation. Educational institutions in Bogota have welcomed students from different contexts, historical backgrounds and ways of perceiving the world. This has caused a variety of conflicts, with different degrees of complexity and resolution mechanisms; this situation can generate a possible discomfort in the school environment and institutional development